Academic hardness of distinguished middle school students - Assis. Lect. Ali Abdul Reda Aliwi (Journal of College of Education, 2023)
The current research aims to identify:• The level of academic perfectionism among outstanding middle school students.• Significance of statistical differences according to the gender variable (male, female).To achieve the objectives of the current research, the researcher translated the Benishek & Lopez scale (2001), consisting of (19) items, and applied it to the basic research sample of (200) male and female students. The results showed that the distinguished middle school students enjoy a high level of academic solidity. There are no statistically significant differences according to the gender variable (males, females), and based on these results, the researcher developed a set of recommendations and proposals.
Keywords: academic solidity, middle School, Outstanding students